PERUBAHAN KEWENANGAN PENERBITAN IZIN USAHA PERTAMBANGAN (IUP) DALAM PERSPEKTIF KEADILAN LINGKUNGAN - Moh Haris Pratama; Syamsuddin Baco; Mohammad Hatta Tampubolon (TADULAKO MASTER LAW JOURNAL, 2025)
This study analyzes the shift in licensing authority for Mining Business Licenses (MBL) from the perspective of environmental justice, focusing on environmental protection, community participation, and local government rights in natural resource governance. Using a normative juridical approach and a case study in Central Sulawesi, the research reveals that recentralization policies weaken local governments and limit public engagement, especially among indigenous peoples and vulnerable groups. The distancing of licensing processes from local access undermines procedural justice and reinforces corporate dominance. Although environmental regulations exist, their implementation remains weak due to poor coordination and limited enforcement capacity. The consequences include environmental degradation, social conflict, and intergenerational injustice. The study concludes that the current licensing regime undermines the principles of decentralization and public participation and recommends strengthening the role of local governments and ensuring legal protections for community involvement in fair and sustainable mining governance.